The Influence of Incorporating Modern Technologies into The Legal Curriculum as Effective Teaching Approach in Higher Education - Bhushan, Tripti (Indonesian Journal of International Law, 2022)
Higher education has seen a tremendous increase in the use of technology in teaching and learning. In this context, technology would play an important part in the law school curriculum inside and outside the classroom. This would allow students to explore various aspects of the legal world beyond the classroom, and the integration provides law schools with a potent weapon. Therefore, this research focused on using technology in teaching and learning, which would significantly aid in addressing law students’ learning requirements. By examining successful technology, it uncovered the gaps between the usage and understanding of International Law. The curriculum offered focused on the position of the law office. Furthermore, this research intended to demonstrate the benefits of incorporating technology into the international law curriculum as an effective teaching approach. It focused on the roles of International Law in responding to advances as a regulator of emerging technology. In an increasingly interconnected world, new technology raised legal issues concerning its use, distribution, and control.